A Novel Spectrophotometric Method for Determination of Chloramphenicol Based On Diazotization Reaction at Room Temperature - Abdul Wafi; Ganden Supriyanto; Tjitjik Srie Tjahjandarie (Indonesian Journal of Chemistry, 2016)
An analytical method for determination of chloramphenicol (CAP) based on the diazotization reaction at room temperature has been developed. The CAP was reduced using zinc powder (Zn) and diazotization reaction was carried out at room temperature in the presence of NaNO2, bismuth nitrate pentahydrate (Bi(NO3)3.5H2O) as catalyst. 2-napthol was used as coupling agent to form a red-violet solution and the absorbance was measured by UV-Vis spectrophotometer at 554 nm. The optimization of analytical parameters including reducing agent, catalyst, coupling agent and time response were 0.15 g, 0.15 g, 230.67 µg/mL and 8-9 min respectively.